Analysis Of Factors Affecting Debt Policy In Transportasi And Logistic Companies - Aliyah, Dini Rahma; Br.Bangun, Mudtiani Hakim; Fazria, Rizka Fazria; Azzahra, An Suci Azzahra (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the factors that influence debt policy in transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2019 to 2023. The main focus of this study is to evaluate the effect of profitability, liquidity, asset structure, and company growth variables on debt policy. The method used in this research is multiple linear regression analysis, with secondary data taken from the financial statements of listed companies. The research sample consists of 22 companies that meet certain criteria through a purposive sampling approach. The results showed that the liquidity variable has a significant influence on debt policy, which indicates that companies with better liquidity tend to have a more conservative debt policy. On the other hand, profitability, asset structure, and firm growth variables do not show a significant influence on debt policy. This study also suggests the need for further research to explore other factors that may affect debt policy in the transportation and logistics sector.